PENGARUH DIGITAL MARKETING, MANFAAT, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PENGGUNAAN LAYANAN GO-PAY : STUDI KASUS PADA KONSUMEN JAKARTA TIMUR - Harahap, Indah Juwita (Jurnal Pijar, 2025)
The purpose of this study is to determine the influence of Digital Marketing, Benefits, and Trust on the Decision to Use Go-Pay services among consumers in East Jakarta. The research approach employed is a descriptive quantitative method. The study sample consists of 250 respondents, analyzed using the Structural Equation Model (SEM). The results show that the Digital Marketing variable (X1) does not have a positive and significant influence on the Decision to Use (Y). Benefits (X2) have a positive and significant influence on the Decision to Use (Y). Trust (X3) also has a positive and significant influence on the Decision to Use (Y).